Go Tell It : How James Baldwin Became a Writer - Harris, Quartez; James, Gordon C. (New York : Little, Brown and Company, 2025)
"A boy who loves stories grows into a teenager who escapes into his writing and then a young man who plays his typewriter like a piano to show the fullness of Black life, in this lyrical picture book biography of James Baldwin, the celebrated novelist, essayist, playwright, poet, and activist"--
Includes bibliographical references.
Keywords: Baldwin, James, -- 1924-1987 -- Juvenile literature; Baldwin, James, -- 1924-1987.; Authors, American -- Biography -- 20th century; African American authors -- Biography; Civil rights workers -- Biography -- United States; Authors, American -- Biography; African American authors -- Biography; Picture books; Biographies